School children preference among foods cooked and served in public primary school canteens in urban and peri-urban areas in Southern Benin - Bodjrenou, Fifali; Amoussa Hounkpatin, Waliou; Termote, Céline (Elsevier, 2023)
Objectives: Many countries are implementing school feeding programs aiming at improving feeding practices, nutritional status and educational performance of children. This study aims at evaluating the appreciation of students on the food cooked in school canteens in three urban and suburban communes namely Cotonou, Abomey-Calavi and Sèmè-Kpodji within the framework of the National Integrated School Feeding Program (PNASI) implemented in Benin by the Government and the WFP. Methods: Twelve public primary schools were randomly selected from the list of schools benefiting from PNASI in the three communes. Individual interviews were conducted with 759 schoolchildren among their appreciation and preference of foods cooked and served in school canteens. Results: Thirteen different types of food made from maize, rice, lentils, cowpea and gari were prepared in canteens. The most preferred were: jollof rice or rice-macaroni mix, boiled lentil, and boiled rice with sauce. These foods were cited in the Top 3 favorite foods by 56.9%, 47.7% and 39.5% of schoolchildren respectively. The least favorite foods were Zankpiti of cowpea (mix of maize flour, beans and red palm oil), macaroni and piron (gari dough) plus sauce; mentioned in the Top 3 of the most appreciated foods by only 1.6%, 0.3% and 0.1% respectively. The main criteria for appreciating foods were flavor and satiating character. Nutritional considerations were secondary. Indeed, Zankpiti, a high-nutrient dense food, was less appreciated; recipes integrating vegetables notably leafy vegetables were not present in the Top favorite foods. Conclusions: Rice recipes were the most appreciated by schoolchildren. Results highlighted importance of considering children perceptions and opinions when modeling school feeding programs. A nutrition education program is also needed to improve nutritional and organoleptic quality of recipes used in school canteens as well as the knowledge and perceptions of schoolchildren about nutrition.